The protective effects of Telfairia occidentalis on potassium bromate induced hepatotoxicity in adult Wistar rats - Busuyi Kolade, Akinola; Toluwase Solomon, Olawuyi; Adesua Emmanuel, Ogunmokunwa (African Science Publications, 2020)
Potassium bromate (KBrO3) used widely in foods have been classified as known human carcinogen with various complications associated with its use. Telfairia occidentalis is a medicinal plant with a number of pharmacological activities attributed to its extracts. This study was designed to investigate the protective effects of Aqueous Extract of Telfairia occidentalis (AETO) on potassium bromateinduced hepatotoxicity in adult Wistar rats. 20 Wistar rats obtained from the Animal House of the Biochemistry Department, FUTA, were acclimatized for one week. They were divided into four groups of five rats each. Group A received distilled water, Group B received 100 mg/kg body weight (b.w.) of KBrO3, Group C received 100 mg/kg b.w. of KBrO3 and 200 mg/kg b.w. of AETO, and Group D received 100 mg/kg b.w. of KBrO3 with 500 mg/kg b.w. of AETO concomitantly for 21 days. Results obtained revealed that exposure of rats to KBrO3 caused loss of normal histoarchitecture, hepatocellular injury and degeneration as well as decreasing hematological parameters. However, administration of AETO with KBrO3 ameliorated the induced-hepatic injury at the same time increasing the hematological parameters. Conclusively, AETO offer protective effects by restoring the structural integrity of the liver and increasing the level of blood parameters which was initially decreased by KBrO3.
Keywords: Potassium bromate, Telfairia occidentalis, Hepatotoxicity, Hematolology